2017
DOI: 10.1596/1813-9450-8209
|View full text |Cite
|
Sign up to set email alerts
|

Oil Discovery and Macroeconomic Management: The Recent Ghanaian Experience

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Problematically, these three motives require quite different types of 20 Similar challenges have proven too much for other countries, such as Ghana and especially Chad. See, for example, Bawumia and Halland (2017). 21 A 2016 blog compared the cases of Norway-the benchmark of successful SWFs-and Tanzania.…”
Section: A Sovereign Wealth Fundmentioning
confidence: 99%
“…Problematically, these three motives require quite different types of 20 Similar challenges have proven too much for other countries, such as Ghana and especially Chad. See, for example, Bawumia and Halland (2017). 21 A 2016 blog compared the cases of Norway-the benchmark of successful SWFs-and Tanzania.…”
Section: A Sovereign Wealth Fundmentioning
confidence: 99%
“…This shortfall was caused, among others, by high oil revenue expectations, election-related overexpenditure, and the implementation of the single-spine salary structure. According to Bawumia and Halland (2017), although the fiscal deficit fell from 6.2 per cent in 2010 to 4 per cent in 2011, it deteriorated again to 9.3 per cent in 2014. IMF (2014) estimates that although government taxes in Ghana averaged 18.9 per cent of GDP from 2010 to 2014, government expenditure increased from 20.1 per cent in 2010 to 28.2 per cent in 2014.…”
Section: Oil and Macroeconomic Performancementioning
confidence: 99%
“…Indeed, Younger (2016) has suggested that expenditure on personal emoluments increased by 1.6 per cent of GDP between 2010 and 2012 while the average contribution to GDP of oil over the same period was 1 per cent. Although Ghana chalked up some legal and regulatory successes in the initial stages of oil production, there were serious concerns about rising public debt, declining capital expenditure, and a deteriorating external payment position (Bawumia and Halland 2017). Figure 5.4 shows Ghana's inflation trends for 1990-2016.…”
Section: Oil and Macroeconomic Performancementioning
confidence: 99%
“…Putting the right rules and government institutions in place is a difficult task, and one that is exacerbated by the challenge of doing so in a highly politicized context. Political cycles can often endanger reform agendas, and populist politics can create pressures for wasteful spending or inequitable distribution strategies, see Collier 2017 andBawumia andHalland 2017. The record in recent years has not been good (Venables, 2016).…”
mentioning
confidence: 99%
“…This can be due to vested interests, their inherent reluctance to give up power and the fact that it can become harder to dislodge incumbents who now possess extensive rents to support their campaigning; for example, see Bawumia and Halland 2017. Third, resource wealth can serve to undermine the very institutions that need to be strong and strengthened during the period of resource exploitation. Governments seeking to meet public expectations or political commitments for increased spending, including on public goods, may be tempted to pressure Central Banks to play a more political role-such as occurred in Ghana after its discovery of oil in 2007; see Bawumia and Halland 2017. Such pressure can undermine the independence of such institutions, weakening their strength to pursue their main objectives of monetary prudence and price stability more generally.…”
mentioning
confidence: 99%